The Use of the Ombudsman's Services for Alleviating International Students' Difficulties - Katsara, Ourania (Journal of International Students, 2015)
This article offers some suggestions regarding the development of a support strategy by ombudsmen in order to alleviate international students' difficulties when studying in host universities. It is also shown how the Organisational Justice Theory can be used as a framework for understanding the role of ombudsman in higher education settings and how this theory underlines the importance of informational power as a remedy to alleviate the students' difficulties. The main implication drawn from the discussion is that cultural variables may suggest specific care on designing appropriate support strategies where the role of Information Communication Technology (ICT) could be explored. Finally, the article offers some suggestions and a service plan showing how power perceptions of the service provider can impact the students' reaction to the quality of the service.